2023
DOI: 10.3389/fonc.2023.1198592
|View full text |Cite
|
Sign up to set email alerts
|

Retroperitoneal abscess as a presentation of colon cancer: The largest case set analysis to date, which extracted from our unit and the literature

Junmin Zhou,
Songlin Wan,
Chunguang Li
et al.

Abstract: ObjectiveColon cancer with retroperitoneal abscess is a rare and easily misdiagnosed disease and has only been reported via case. There is an urgent need to conduct a dataset analysis for such patients, which is crucial to improving the survival rate and quality of life of these patientsMethodsPatients with colon cancer associated with retroperitoneal abscess were extracted from our hospital and the PubMed, EMBASE and Web of Science databases. Clinical information, including the patients’ basic characteristics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Another case is of a 50-year-old woman diagnosed primarily with abscess in the Douglas pouch and ovarian cancer, however, subsequent workup revealed 5.5-cm-diameter round mass was located adjacent to the sigmoid colon in the pelvic cavity and was diagnosed with an abscess and sigmoid colon cancer [8]. In a case analysis by Zhou et al, 61 patients with 98% having a diagnosis of CRC were studied [9]. The study identified 87.2% of patients had an iliopsoas muscle abscess, and CT imaging did not detect simultaneous tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Another case is of a 50-year-old woman diagnosed primarily with abscess in the Douglas pouch and ovarian cancer, however, subsequent workup revealed 5.5-cm-diameter round mass was located adjacent to the sigmoid colon in the pelvic cavity and was diagnosed with an abscess and sigmoid colon cancer [8]. In a case analysis by Zhou et al, 61 patients with 98% having a diagnosis of CRC were studied [9]. The study identified 87.2% of patients had an iliopsoas muscle abscess, and CT imaging did not detect simultaneous tumors.…”
Section: Discussionmentioning
confidence: 99%